Resveratrol-Based Nanoformulations as an Emerging Therapeutic Strategy for Cancer - Sharifi-Rad, Javad; Quispe, Cristina; Mukazhanova, Zhazira; Knut, Ewa; Turgumbayeva, Aknur; Kipchakbayeva, Aliya; Seitimova, Gulnaz; Mahomoodally, Mohamad Fawzi; Lobine, Devina; Koay, Aaron; Wang, Jinfan; Sheridan, Helen; et al. (Frontiers in Molecular Biosciences, 2021)
Resveratrol is a polyphenolic stilbene derivative widely present in grapes and red wine. Broadly known for its antioxidant effects, numerous studies have also indicated that it exerts anti-inflammatory and antiaging abilities and a great potential in cancer therapy. Regrettably, the oral administration of resveratrol has pharmacokinetic and physicochemical limitations such as hampering its effects so that effective administration methods are demanding to ensure its efficiency. Thus, the present review explores the published data on the application of resveratrol nanoformulations in cancer therapy, with the use of different types of nanodelivery systems. Mechanisms of action with a potential use in cancer therapy, negative effects, and the influence of resveratrol nanoformulations in different types of cancer are also highlighted. Finally, the toxicological features of nanoresveratrol are also discussed.